Prediction of the feeding background of Iberian pigs using the fatty acid profile of subcutaneous, muscle and hepatic fat. (Meat science, 1998)
Thirty Iberian pigs weighing 95 kg were randomly distributed into three groups of 10 animals each and fattened in three traditional management systems ['montanera' (MO), fed extensively on acorns, 'cebo' (CE) fed on a commercial diet and 'recebo' (RE), fed on acorns and a commercial diet]. Fatty acids from the Masseter muscle, lard and liver were analysed. In the lard, fatty acid profiles from MO and RE pigs presented minor differences; however, in the liver, RE pigs showed differences to MO pigs in most of the fatty acids studied. This suggests that the muscle and especially the liver fatty acid profile reflects the feeding regime during the last phase of feeding, while the lard reflects longer term differences.

Influence of finishing diet on fatty acid profiles of intramuscular lipids, triglycerides and phospholipids in muscles of the Iberian pig. (Meat science, 1997)
Thirty Iberian × Duroc pigs allotted in groups of ten animals were fed in three traditional different management systems ('Montanera' (MO), fed on acorns; 'Recebo' (RE), fed on acorns and a commercial diet; and 'Cebo' (CE), fed on a commercial diet). Masseter muscle was obtained to evaluate the influence of management system on fatty acid (FA) composition of lean. The FA composition of the intramuscular total lipids, triglyceride (TG) and phospholipid (PL) fractions was evaluated. Muscle from MO pigs had greater quantities of monounsaturated fatty acids (MUFA) in the total lipids, triglyceride and phospholipid fractions than the other feedings. The percentage of saturated fatty acids (SFA) of i.m. total lipids and TGs increased (P < .05) with duration of feeding on RE and CE, from 35.13-35.10% in MO pigs to 37.47-37.84% in RE pigs and 39.98-41.11% in CE pigs. PLs from RE and CE pigs contained more C(18:2) and C(20:4) and less C(18:1) than MO pigs.